2014
DOI: 10.1902/jop.2013.130306
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Analysis of Subgingival Plaque Samples Compared to That of Whole Saliva in Patients With Periodontitis

Abstract: Objectives The purpose of this study was to compare microbial profiles of saliva, pooled and site-specific subgingival samples in patients with periodontitis. We tested the hypotheses that saliva can be an alternative to pooled subgingival samples, when screening for presence of periopathogens. Design Site specific subgingival plaque samples (n = 54), pooled subgingival plaque samples (n = 18) and stimulated saliva samples (n = 18) were collected from 18 patients with generalized chronic periodontitis. Subging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 43 publications
9
77
0
1
Order By: Relevance
“…Previous studies have shown positive associations between the levels of periodontal pathogens in saliva and in subgingival plaque 4 and between the detection of periodontal pathogens in the saliva and the degree of gingival inflammation. 5 Considering that saliva collection is a simple, safe, economical, and noninvasive method, it should be a useful medium for monitoring oral pathogen levels during orthodontic treatment.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have shown positive associations between the levels of periodontal pathogens in saliva and in subgingival plaque 4 and between the detection of periodontal pathogens in the saliva and the degree of gingival inflammation. 5 Considering that saliva collection is a simple, safe, economical, and noninvasive method, it should be a useful medium for monitoring oral pathogen levels during orthodontic treatment.…”
Section: Introductionmentioning
confidence: 94%
“…Environmental transitions in the subgingival crevice as periodontal disease develops have been demonstrated to trigger significant alterations in both the host and T. denticola transcriptome (Bakthavatchalu et al 2011;Haririan et al 2014;Jonsson et al 2011). However, the regulatory pathways and effectors that control adaptive responses are relatively unknown.…”
Section: Two Component Regulatory Systems and Adaptive Responses Of Tmentioning
confidence: 99%
“…A previous study yielded kappa values of 0.40 and 0.59 for detection of T. forthysia and T. denticola from saliva and subgingival plaque (48). This study also used pooled subgingival plaque samples from the deepest pocket in each quadrant.…”
Section: Discussionmentioning
confidence: 99%